Find f(g(x)) f(x)=4x-1 g(x)=3x^3-1

Math
Set up the composite result function.
Evaluate by substituting in the value of into .
Simplify each term.
Tap for more steps…
Apply the distributive property.
Multiply by .
Multiply by .
Subtract from .
Find f(g(x)) f(x)=4x-1 g(x)=3x^3-1


Need help with MATH HOMEWORK

We can help your. Our mathematic problem solver answers your math homework questions with step-by-step explanations.

Need help with math? Try to Solve Algebra Math Problems here: https://elanyachtselection.com/

Scroll to top